The Effect of Working Environment and Discipline on Employee Performance at Bravia Cash & Credit Cikarang - Putri Wardah; Rycha Kuwara Sari (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
Effect of Working Environment and Discipline on Employee Performance at Bravia Cash & Credit Cikarang. This study aims to determine the effect of work environment and work discipline on the performance of Bravia Cash & Credit Cikarang employees. This type of research is quantitative research. The objects in this study are employees of Bravia Cash & Credit Cikarang with a population of 38 and the sample calculation is determined by the saturated sample formula. The analytical tool in this research is using SmartPLS 3.0 to test the feasibility of the research method and test the hypothesis. Partial test results of working environment variables and discipline on performance show that working environment and work discipline variables have a positive and significant effect on employee performance.